Analysis and comparison of business intelligence tools most preferred by companies in Turkey - YILDIZ, KAZIM; ÜLKÜ, EYÜP EMRE (My University, 2023)
With the development of technology and the increase of the data sources, the size and variety of data collected from these sources has increased considerably. Thus, individuals and institutions have become able to store more data. However, it has become an important need to make meaning from this large and valuable data and transform into information and has become more complex. Business intelligence applications ensure that different types of data collected from different data sources are clustered and separated in a certain order and it provides the creation of reports by establishing a semantic relationship between these stored data. The aim of this study is identifying the business intelligence tools preferred by companies in Turkey. It is also aimed to give ideas to institutions and individual users so that they can choose the right business intelligence tool. Within the scope of the study, first of all, the general definition of business intelligence and the business intelligence applications preferred by the companies in Turkey in recent years are mentioned. Afterwards, the information obtained from the scanned scientific studies are analyzed and the findings are presented and then these tools were compared with the tables and it was aimed to give an idea to individuals and institutions. Scientific studies are very important in terms of revealing the current status of these business intelligence tools and seeing what kind of studies they can be used in the future.
Keywords: — Business Intelligence; Qlik; Power BI; SAP BO; Tableau